Mind mapping by canva as a digital media: A Class Action Research (CAR) in geography learning - Azis, Daska; Suhendro; Yazid Saleh; Muhammad Al-Farisy; Furqan, M. Hafizul; Salda, Athala Rania; Gadeng, Ahmad Nubli; Hadiyani, Rahmilia; Sadida, Ade Nailan; SP, Ade Asyifa (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Mind Mapping learning model is designed to help students recognize, understand, and retain information more efficiently. This classroom action research aims to evaluate the impact of this model on student learning outcomes, teacher activities, teaching effectiveness, and student responses. This study used a classroom action research method with a process of two cycles of learning activities. The study involved 33 students from at SHS 1 Tapaktuan, South Aceh, Indonesia with data collected through pre-tests and post-tests, teacher and student activity observations, teacher skill assessments, and student response questionnaires. Simple analysis such as percentages were used in processing the data obtained. The findings indicate that individual learning mastery increased from 75% in Cycle I to 93% in Cycle II, while class-wide mastery improved from 60% to 90%. Additionally, teacher and student engagement showed a significant improvement, rising from 63.3% in Cycle I to 100% in Cycle II. Teaching effectiveness also improved, with teacher performance scores increasing from 3.25 (good) in Cycle I to 3.5 (very good) in Cycle II. Students responded very positively to the Mind Mapping model assisted by Canva media, with 86% of students stating that this method helped them understand the material better. Based on these findings, the Mind Mapping model, integrated with Canva media, has been proven to be an effective approach for enhancing Geography learning outcomes among Class X-B students.